Decentralization and Subnational Service Delivery in Iraq : Status and Way Forward - World Bank (World Bank, Washington, DC, 2016)
Since the Constitution (2005) provided for decentralizing powers and functions for the Governorates, the government of Iraq has enacted several legal, policy, and institutional reform initiatives, the intent of which is to shift political and administrative powers and responsibilities from the Central Government to the Governorates. The legal and policy framework for decentralization is yet to be followed through with efficient implementation. The Government of Iraq and the World Bank will like to assess the current status of decentralization and its implications for improving service delivery at the Governorate level. The objective of the assessment is to take stock of the current state of decentralization in Iraq with a view to identifying factors that contribute to weak service delivery performance at the governorate level. The assessment will also make recommendations for policy and process reforms that are deemed necessary to moving forward the decentralization process, thereby helping to improve service delivery performance by the Governorates. The assessment was carried out through a combination of desk reviews and field level consultations. This assessment provides a snapshot of the current status of the decentralization process. It identifies policy and process reform measures that are necessary to strengthen service delivery by the 15 Governorates of Iraq. Strengthening local accountability should be the key to strengthening the service delivery performance of the Governorates.